Unpacking Cultural Hybridity and Diasporic Femininity in Jhumpa Lahiri's The Lowland - R, Dr. Murugan (South Eastern European Journal of Public Health, 2024)
This paper aims to illustrate the traumas, moral quandaries, sorrows, and, in the end, the cultural hybridity of diasporic women found in Jhumpa Lahiri’s The Lowland. Her novel helps us understand the psyche of these women of a new age since it resonates to them. Lahiri depicts a fusion of politics, history, and their impact on a family's life in The Lowland. The novel has been loosely drawn on a large canvas to depict the multigenerational tale of personal goals and choices. This novel portrays the international diasporic culture of the twenty-first century as well as the multiculturalism and metamorphosis of the immigrants. Because her female protagonists accurately depict the diasporic difficulties that affect them in daily life - such as cultural tensions, marginalization, family relationships, customs, rituals, a sense of not belonging, transformation, and adaptation - this study is extremely important.